2008
DOI: 10.2139/ssrn.1295610
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Popularity of Online Content

Abstract: We present a method for accurately predicting the long time popularity of online content from early measurements of user's access. Using two content sharing portals, Youtube and Digg, we show that by modeling the accrual of views and votes on content offered by these services we can predict the long-term dynamics of individual submissions from initial data. In the case of Digg, measuring access to given stories during the first two hours allows us to forecast their popularity 30 days ahead with remarkable accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
154
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(158 citation statements)
references
References 22 publications
(11 reference statements)
2
154
0
2
Order By: Relevance
“…Here, we used a news life-cycle as the content model as it is a striking instance of dynamic content models. Since many newsworthy events are generated in a day [11]- [13] and instantaneous reports are important for news articles [14], [15], the frequency of generation of news content is higher and the change in the popularity of content is much more frequent those for entertainment.…”
Section: News Content Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we used a news life-cycle as the content model as it is a striking instance of dynamic content models. Since many newsworthy events are generated in a day [11]- [13] and instantaneous reports are important for news articles [14], [15], the frequency of generation of news content is higher and the change in the popularity of content is much more frequent those for entertainment.…”
Section: News Content Modelmentioning
confidence: 99%
“…Therefore, the rate of decline in the request probability of news content is sharper than that in entertainment content and does not follow Zipf's law. Some conventional research has analyzed and reported the life cycle of news articles [14]- [18]. Most of them can be approximated by monotonic decrease models.…”
Section: Request Probabilitymentioning
confidence: 99%
“…Also, our work is focused on generic events unlike movie forecasts (Asur and Huberman, 2010) where specific features like Hollywood Stock Exchange time series could be exploited as features. Besides Twitter, there has been work on future popularity of social media content on Digg and Youtube (Lerman and Hogg, 2010;Szabo and Huberman, 2010). But, the design of the user interface of Twitter and Digg are quite different resulting in a huge difference in social dynamics of the two networks.…”
Section: Predictive Analysis On Twitter and Other Platformsmentioning
confidence: 99%
“…Using analytical methods from social networks to investigate the macroscopic characteristics of the network of videos, works have studied the impact of user generated content in underlying video-on-demand architectures [6,7], and in local networks [9,23]. By concentrating specifically on videos, research has also studied the daily cycles of video reception (based on the number of views), in an attempt to automatically predict their popularity [22]. In relation to video content, several studies have manually coded samples of videos to categorize the types and properties of YouTube content to gain understanding about user-generated media production [13,12,5].…”
Section: Research In Youtubementioning
confidence: 99%